Practice nurses' communication with people living with type 2 diabetes: A scoping review. Issue 8 (August 2022) - Hills, Sharon; Terry, Daniel; Gazula, Swapnali; Browning, Colette
Abstract: Objective: To identify the key characteristics of practice nurses' communication with people living with Type 2 Diabetes (T2D) where lifestyle activities are discussed. Methods: A scoping review of the peer-reviewed literature was conducted. Reflexive thematic analysis was used to identify key themes that emerged. The PRISMA-ScR checklist was followed. Results: 25 studies were retained in the final review. Nurses who were committed to engaging in lifestyle discussions created supportive environments and built rapport to enable change conversations. However, this was present in just 20% of the studies. In most studies, (60%) nurses continued to use traditional health education communication styles, had little understanding of behaviour change theories, lacked skills in behaviour change counselling and were reluctant to engage in behaviour change discussions with people with T2D . Conclusions: Nurses require a deeper understanding of behavioural change theories and skills in behavioural counselling. Practice implications: Practice nurses have a unique opportunity to facilitate T2D remission by engaging in evidence-based behaviour change communication. A behaviour change training intervention is needed that recognises the environment of practice nurse consultations. It needs to be pragmatic and fully consider the enablers and barriers to addressing behaviour change in both the nurse and the person with T2D. Highlights: Practice nurses continue to use traditional health education communication styles. Practice nurses can assist people with T2D to achieve lifestyle change. Skills in behavioural counselling are required to engage in these conversations. Developing skills in behavioural counselling may positively facilitate T2D remission.